2023
DOI: 10.5946/ce.2022.020
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic removal of common bile duct stones in nonagenarians: a tertiary centre experience

Abstract: Background/Aim: There are few studies assessed the efficacy and mortality of endoscopic retrograde cholangiopancreatography (ERCP) for the removal of common bile duct (CBD) stones in the elderly aged ≥90 years. We aimed to assess the safety and efficacy of endoscopic removal of CBD stones in nonagenarians. Methods: We retrospectively reviewed ERCP reports for CBD stone removal. The endoscopic and therapeutic outcomes were collected. The length of stay (LOS), the total number of adverse events, and mortality ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…In older adults, attention should be paid to post-procedural pneumonia. In 2023, a retrospective study showed that patients aged ≥90 years who underwent ERCP for CBD stone removal had a higher incidence of post-ERCP pneumonia than those aged 65-89 years [11]. In addition, there is a report that patients aged ≥90 years require particular attention among the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…In older adults, attention should be paid to post-procedural pneumonia. In 2023, a retrospective study showed that patients aged ≥90 years who underwent ERCP for CBD stone removal had a higher incidence of post-ERCP pneumonia than those aged 65-89 years [11]. In addition, there is a report that patients aged ≥90 years require particular attention among the elderly.…”
Section: Discussionmentioning
confidence: 99%